Luis Alvarez : Wild idea man - Venezia , Mike; Venezia , Mike (New York : Scholastic, 2010)
A short biography of physicist Luis Alvarez.
Keywords: Alvarez , Luis W ., 1911 -- Juvenile Literature; Physicsists- United States- Biography -- Juvenile Literature